Shoulder Impingement - Tagg, Catherine E.; Campbell, Alastair S.; McNally, Eugene G. (Seminars in Musculoskeletal Radiology, 2013)
This update examines recent articles and evidence for the role of ultrasound in the diagnosis and management of shoulder impingement syndromes and emphasizes its principal application in evaluation for external impingement. Shoulder ultrasound is commonly used as the initial investigation for patients with shoulder pain and suspected impingement. This is due to the high resolution of current ultrasound machines, wide availability, good patient tolerance, cost effectiveness, and, most importantly, its dynamic and interventional role.
Keywords: shoulder; ultrasound; impingement